Impact of induction therapy on outcomes after heart transplantation. (14th October 2021) - Briasoulis, A; Doulamis, I; Kampaktsis, P; Alvarez, P
Abstract: Introduction: Approximately 50% of heart transplant (HT) programs currently employ a strategy of induction therapy (IT) with either interleukin-2 receptor antagonists (IL2RA) or polyclonal anti-thymocyte antibodies (ATG) during the early postoperative period. However, the overall utility of such therapy is uncertain and data comparing induction protocols are limited. Methods: Adult HT recipients were identified in the United Network for Organ Sharing (UNOS) registry between 1990 and 2020. Patients were grouped according to administration of induction in the post-operative period after HT. Accounting for re-transplantation, Fine and Gray's test compared cumulative incidences of all-cause mortality between groups. Univariate and multivariate analysis were performed using the competing risk model. The risk of treated rejection and hospitalization for infection or rejection was analyzed with multivariable logistic regression. Results: A total of 63, 849 HT recipients were included in the study and among those 59% did not receive induction, 16.6% received ATG, 19.1% IL2RA, 0.7% alemtuzumab, and 4.6% OKT3. Since 2000 IL2RA is the most frequently used form of induction therapy whereas OK3 is not used in the past decade. In multivariable logistic regression models, use of ATG is associated with lower risk of treated rejection at one year after HT (relative risk ratio 0.55, 95% CI 0.47–0.63, p<0.001) compared with no induction whereas IL2RA had similar risk of treated rejection. Similarly, the risk of rejection requiring hospitalization was significantly lower with ATG than no induction. No significant differences in rates of infection requiring hospitalization were noted between groups. Moreover, no differences in rates of post-transplant lymphoproliferative disease and any malignancy were noted between those receiving induction versus no induction. Adjusted all-cause mortality was significantly lower among those treated with ATG than patients that did not receive induction therapy (sub-hazard ratio 0.72, 95% CI 0.63–0.82, p<0.001) (Figure). Conclusion: Induction therapy with IL2RA is the most used approach. ATG is associated with lower risk of treated rejection and all-cause mortality than no induction and IL2RA. Funding Acknowledgement: Type of funding sources: None.